Highly Sensitive, Flexible MEMS Based Pressure Sensor with Photoresist Insulation Layer. Issue 44 (29th September 2017) - Liang, Binghao; Chen, Wenjun; He, Zhongfu; Yang, Rongliang; Lin, Zhiqiang; Du, Huiwei; Shang, Yuanyuan; Cao, Anyuan; Tang, Zikang; Gui, Xuchun
Abstract: Pressure sensing is a crucial function for flexible and wearable electronics, such as artificial skin and health monitoring. Recent progress in material and device structure of pressure sensors has brought breakthroughs in flexibility, self‐healing, and sensitivity. However, the fabrication process of many pressure sensors is too complicated and difficult to integrate with traditional silicon‐based Micro‐Electro‐Mechanical System(MEMS). Here, this study demonstrates a scalable and integratable contact resistance‐based pressure sensor based on a carbon nanotube conductive network and a photoresist insulation layer. The pressure sensors have high sensitivity (95.5 kPa −1 ), low sensing threshold (16 Pa), fast response speed (<16 ms), and zero power consumption when without loading pressure. The sensitivity, sensing threshold, and dynamic range are all tunable by conveniently modifying the hole diameter and thickness of insulation layer. Abstract : A highly sensitive, flexible MEMS based pressure sensor is developed by a scalable and integratable method. This pressure sensor shows excellent performance in sensitivity and response speed. Besides, it possesses the characteristics of ultralow power consumption and is suitable for integration. The potential application as a high space resolution sensor matrix is demonstrated.